Hand‐held health records for individuals with intellectual disability: a systematic review. (1st December 2013) - Nguyen, M.; Lennox, N.; Ware, R.
Abstract Background Hand‐held health records (HHHRs) aim to empower individuals with intellectual disability (ID) and improve the communication between all those involved in their health care. HHHRs can be used to identify additional health needs and contribute to improved treatment for individuals with ID. This review summarises evidence concerning the use of HHHRs with individuals with ID. Methods Systematic searching of electronic databases and email contact with established researchers in the field were used to identify relevant articles related to the use of HHHRs among individuals with ID. Results Seven articles were identified and included for review. Studies involved the development, evaluation, acceptability and facilitators and barriers of implementation of HHHRs. HHHRs did not lead to improved short‐term healthcare activity, but did lead to more discussion about health problems, increased health‐related knowledge and awareness of personal health issues. Conclusions HHHRs are well accepted among users with ID. However, no short‐term benefits were found and future research needs to examine the long‐term effects of HHHRs.